Bioadhesive microspheres for bioavailability enhancement of raloxifene hydrochloride: Formulation and pharmacokinetic evaluation - Jha R.K.; Tiwari S.; Mishra B. (My University, 2025)
Raloxifene hydrochloride (R-HCl), a BCS class II drug, remains a mainstay in the prevention and pharmacologic therapy of osteoporosis. Its absolute bioavailability, however, is 2% due to poor solubility and extensive first pass metabolism. The present study describes two simultaneous approaches to improve its bioavailability, complexation of R-HCl with cyclodextrin(s), and formulation of mucoadhesive microspheres of the complex using different proportions of carbopol and HPMC. Microspheres were pale yellow in color, free-flowing, spherical, and porous in outline. The particle size ranged between 3 and 15 μm, and entrapment efficiency was found to be within 81.63% to 87.73%. A significant improvement in the solubility of R-HCl was observed, and it differed with the combination of excipients used. X-ray diffraction and differential scanning calorimetry studies revealed that enhancement in drug solubility was resulted due to a change in its crystallinity within the formulation. Microspheres possessed remarkable mucoadhesion and offered controlled drug release, lasting up to 24 h. They produced a sharp plasma concentration-time profile of R-HCl within 30 min postadministration to Wistar rats. [AUC]0-24 h was found to be 1,722.34 ng h/ml, and it differed significantly to that of pure drug powder (318.28 ng h/ml). More than fivefold increase in AUC and more than twofold increase in MRT were observed. FT-IR studies evidenced no interaction among drug and excipients. The results of this study showed that mucoadhesive microspheres could be a viable approach to improve the pharmacokinetic profile of R-HCl. © 2011 American Association of Pharmaceutical Scientists.